O fazer do psicólogo no núcleo de apoio à saúde da família - Cela, Mariana (2014)
The Brazilian Ministry of Health regulated in 2008 the Family Health Support Nucleus (FHSN) as a device for support and complementarity to the Family Health Strategy. The FHSN, through the matrix support, potentiates the Family Health teams on dealing with a great variety of demands and activities that are under their responsibilities. It is structured in teams of professionals from various health specialties, among which is the mental health. In preliminary studies we noticed that the psychologists have been the main representatives of mental health professionals at the FHSN from Rio Grande do Norte (RN-Brazil). On this scenario, this study intends to problematize the professional practice of the psychologists who work at the FHSN teams in RN, regarding how their work is done, discussing it under the perspective of collective health and the directions for the basic health care on Brazilian s health system. Still as a goal, in more specific ways: identify the forms of professional insertion of the psychologists in this field; characterize the work done by the psychologist at the FHSN (developed activities); and produce an analysis of the characteristics and limits of those actions, from theoretical and methodological references based on Marxian ontology. Were performed semistructured interviews with psychologists working in the oldest FHSN teams form RN. We conducted the analysis of the material following the blocks of information: determinants of the psychologist entry at the services, training for current practice; operation of FHSN; activities performed by FHSN team and the psychologist; joint actions; and limits of psychology practice in the FHSN. An important result, we observed the little articulation of practicing between the psychology and other professionals and teams, further indicating the prevalence of the traditional medical model (individual and outpatient) as guidance of their performance instead of the matrix logic that is the foundation of the proposed action for the FHSN. We also emphasize the potential of psychologists actions at the FHSN on contributing to the achievement of comprehensive care